2016
DOI: 10.1155/2016/4583674
|View full text |Cite
|
Sign up to set email alerts
|

The Athlete’s Brain: Cross-Sectional Evidence for Neural Efficiency during Cycling Exercise

Abstract: The “neural efficiency” hypothesis suggests that experts are characterized by a more efficient cortical function in cognitive tests. Although this hypothesis has been extended to a variety of movement-related tasks within the last years, it is unclear whether or not neural efficiency is present in cyclists performing endurance exercise. Therefore, this study examined brain cortical activity at rest and during exercise between cyclists of higher (HIGH; n = 14; 55.6 ± 2.8 mL/min/kg) and lower (LOW; n = 15; 46.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 38 publications
8
40
1
Order By: Relevance
“…Furthermore, Jacobson and Matthaeus found that self-paced athletes outperformed both externally-paced athletes and non-athletes in a task involving inhibitory control [84], which supports the conclusion of Ludyga et al's study [80] suggesting that high fit cyclists might have a better inhibitory control.…”
Section: Level Of Expertisesupporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore, Jacobson and Matthaeus found that self-paced athletes outperformed both externally-paced athletes and non-athletes in a task involving inhibitory control [84], which supports the conclusion of Ludyga et al's study [80] suggesting that high fit cyclists might have a better inhibitory control.…”
Section: Level Of Expertisesupporting
confidence: 72%
“…For instance, Ludyga et al [80] found that cyclists with higher fitness level had less brain cortical activity in comparison to a group of lower fitness level cyclists, during a 30 min submaximal cycling exercise below the ventilatory threshold. We acknowledge that the exercise intensity in this study was fixed, and therefore the results might not extrapolate to a self-paced aerobic exercise.…”
Section: Level Of Expertisementioning
confidence: 99%
“…Untrained individuals recruit additional cortical resources, which might not be essential for performing the task (Babiloni et al, 2010;Del Percio et al, 2011). In this respect, Ludyga et al (2015b) have also shown that cyclists with higher aerobic fitness compared to peers with lower aerobic fitness complete a cycling bout with less cortical activity. In the present study, improvements of maximal oxygen uptake were accompanied by a decrease in cortical activity during exercise only after HCT.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the relation between pedalling frequency and EEG activity (Hottenrott et al, 2013;Schumann & Seibt, 1993), we expected changes in frontal alpha/beta ratio during exercise to occur after HCT only. As a lower level of arousal has been confirmed during an exercise bout of submaximal intensity in cyclists with higher aerobic fitness compared to peers with lower aerobic fitness (Ludyga, Gronwald, & Hottenrott, 2015b), a lowering of the alpha/beta ratio with increased aerobic power was expected.…”
Section: Introductionmentioning
confidence: 90%
“…Thus, greater guitar playing skills correlate with decreased motor cortical activity (on EEG) during planning of motor movements involved in playing; 115 hemodynamic responses (on BOLD fMRI) in professional formula race car drivers are more focused than those in naı¨ve drivers during performance of simple visuo-motor skill tasks; 116 compared to controls, skilled keyboard players show attenuated hemodynamic changes (on BOLD fMRI) in the cerebellum during complex finger movement tasks; 117 less cortical activity (on EEG) is seen in fitter than in less fit cyclists during cycling at the individual anaerobic threshold. 118 In the context of current work, we postulate that chronic elevation of CO 2 levels during sustained exercise may lead to arteriolar desensitization to CO 2 29 as well as a metabolic adaptation leading to increased system's efficiency. 119 We speculate that NO signaling may be the mediator of the arteriolar desensitization given its involvement in hypercapnic vasodilation.…”
Section: Cerebral Vascular Reserve Capacitymentioning
confidence: 93%